IMPLEMENTASI PANCA SOLADALAM MEMBANGUN IMAN DAN KARAKTERMAHASISWA STT SABDA AGUNG DI ERA DIGITAl - Lahagu, Abdiel Anugrah (STT-RAI Batam, 2025)
Technological advances in the digital era provide opportunities for all students to expand their knowledge, develop interests and talents to a wider realm both in terms of spirituality and aspects of knowledge. However, along with rapid technological advances in the digital era, especially in the 21st century, it also presents challenges for students studying in theological schools, one of which is STT Sabda Agung. The rapid development of media and technology in the digital era hinders students in building faith and character. The method used in this research is a research method with a qualitative approach. The purpose of this research focuses on an in-depth understanding of how the principles of panca sola are implemented in the digital era, as well as their influence on the formation of character and faith of STT Sabda Agung students. The results of this study confirm that the principles of “panca sola” in Christian theology have a vital role in equipping theology students. In the midst of the onslaught of digital information and innovation, a true understanding of the Word of God, imbued with sola scriptura, sola fide, sola gratia, sola christo, and soli deo gloria, becomes a compass that guides them to develop faith, deepen knowledge, and form a character that reflects Christ.